Energy and distance adaptive clustering algorithm for 3D wireless sensor networks. (1st January 2013) - Jiang, Nan; Guo, Yan; He, Yueshun
How to use the limited energy of sensor nodes efficiently and evenly is a significant issue which needs an emphatic consideration in the research on wireless sensor networks (WSNs). After researching, we find some factors such as the residual energy of node, and the distance from node to base station (BS) are critical for the network lifetime. Further, combining with the practical application of WSN in three-dimensional space, this paper proposes a three-dimensional solution based on the energy and distance adaptive clustering (3DEDAC) algorithm. In the following simulation experiments, we compare the network lifetime of 3DEDAC with the reconstructive LEACH protocol's from different aspects, and calculate the optimum cluster number of 3D space. These experiment results demonstrate the 3DEDAC algorithm has higher energy efficiency in different network conditions, and is more competent to prolong the network's lifetime.